Current situation of the organisation, resources and activity in paediatric cardiology in Spain - Francisco Sánchez Ferrer; Francisco José Castro García; Javier Pérez-Lescure Picarzo; Ferrán Roses Noguer; Fernándo Centeno Malfaz; María Dolores Grima Murcia; Dimpna Albert Brotons (Elsevier, 2019)
Introduction: The results are presented on the "current situation of the organisation, resources and activity in paediatric cardiology in Spain". It was promoted by the Spanish Society of Paediatric Cardiology and Congenital Heart disease. Material and methods: An analysis was carried out on the results obtained from a specifically designed questionnaire, prepared by the Spanish Society of Paediatric Cardiology and Congenital Heart disease, that was sent to all hospitals around the country that offer the speciality of paediatric cardiology. Results: A total of 86 questionnaires were obtained, including 14 hospitals that perform cardiac surgery on children. A total of 190 paediatric cardiology consultants, 40 cardiac surgeons, and 27 middle grade doctors performing their paediatric residency (MIR programme) were identified. All hospitals had adequate equipment to perform an optimal initial evaluation of any child with a possible cardiac abnormality, but only tertiary centres could perform complex diagnostic procedures, interventional cardiology, and cardiac surgery. In almost all units around the country, paediatric cardiology consultants were responsible for outpatient clinics and hospital admissions, whereas foetal cardiology units were still mainly managed by obstetricians. The number of diagnostic and therapeutic procedures was similar to those reported in the first survey, except for a slight decrease in the total number of closed cardiac surgery procedures, and a proportional increase in the number of therapeutic catheterisations. Conclusions: Paediatric Cardiology in Spain is performed by paediatric cardiology consultants that were trained initially as general paediatricians, and then completed a paediatric cardiology training period. Almost all units have adequate means for diagnosis and treatment. Efforts should be directed to create a national registry that would not only allow a prospective quantification of diagnostic and therapeutic procedures, but also focus on their clinical outcomes. Resumen: Introducción: Presentamos el trabajo «situación actual de la organización, recursos y actividad en cardiología pediátrica en España», promovido por la Sociedad Española de Cardiología Pediátrica y Cardiopatía Congénitas. Material y métodos: El estudio se elaboró con los resultados obtenidos de un cuestionario elaborado por la Sociedad Española de Cardiología Pediátrica y Cardiopatía Congénitas, remitido a todos los hospitales del territorio nacional con actividad en cardiología pediátrica. Resultados: Ochenta y seis respondieron el cuestionario, 14 de los cuales disponen de cirugía cardíaca infantil. Los recursos humanos incluyen 190 médicos, 40 cirujanos y 27 MIR. Todos los hospitales disponen de material para el diagnóstico inicial adecuado, y solo los hospitales terciarios disponen de técnicas de diagnóstico específico, cardiología intervencionista y cirugía cardíaca. La atención a los pacientes, en consultas externas y en la hospitalización es realizada o supervisada mayoritariamente por cardiólogos pediátricos. Existe diversidad en los profesionales que realizan las ecocardiografías fetales, ya que en un porcentaje considerable de hospitales sigue siendo realizada en exclusiva por los obstetras. El número de procedimientos diagnósticos y terapéuticos fueron similares al registro previo, con un leve descenso de cirugía cardíaca cerrada y un aumento proporcional de cateterismos terapéuticos. Conclusiones: La cardiología pediátrica en España es realizada por pediatras con formación en cardiología pediátrica mayoritariamente. La mayoría de los centros disponen de medios adecuados de diagnóstico, y solo los hospitales terciarios cuentan con técnicas de diagnóstico específico, cardiología intervencionista y cirugía cardíaca. En futuros estudios, debemos no únicamente cuantificar las técnicas de diagnóstico y tratamiento sino también, aspirar a la cuantificación de resultados clínicos.